2011
DOI: 10.1016/j.neuroscience.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and individual variation in singing behavior correlates with alpha 2-noradrenergic receptor density in brain regions implicated in song, sexual, and social behavior

Abstract: In seasonally breeding male songbirds, both the function of song and the stimuli that elicit singing behavior change seasonally. The catecholamine norepinephrine (NE) modulates attention and arousal across behavioral states, yet the role of NE in seasonally-appropriate vocal communication has not been well-studied. The present study explored the possibility that seasonal changes in alpha 2-noradrenergic receptors (α2-R) within song control regions and brain regions implicated in sexual arousal and social behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
3
12
0
Order By: Relevance
“…Since steroid hormone levels vary seasonally and with vocal behavior in type I males [Sisneros et al, 2004; Genova et al, 2012], there may yet prove to be plasticity in TH-ir innervation of VMN within male morphs between seasons (and likely between courtship and parental phase within the summer reproductive season in type I males), similar to our findings in the auditory system of females [Forlano et al, 2015]. Compellingly, the density of α 2 -ARs in the song control nuclei of male European starlings varies seasonally, showing an inverse relationship between circulating t estosterone, song nuclei volume, and singing behavior [Riters et al, 2002; Heimovics et al, 2011]. …”
Section: Discussionsupporting
confidence: 80%
“…Since steroid hormone levels vary seasonally and with vocal behavior in type I males [Sisneros et al, 2004; Genova et al, 2012], there may yet prove to be plasticity in TH-ir innervation of VMN within male morphs between seasons (and likely between courtship and parental phase within the summer reproductive season in type I males), similar to our findings in the auditory system of females [Forlano et al, 2015]. Compellingly, the density of α 2 -ARs in the song control nuclei of male European starlings varies seasonally, showing an inverse relationship between circulating t estosterone, song nuclei volume, and singing behavior [Riters et al, 2002; Heimovics et al, 2011]. …”
Section: Discussionsupporting
confidence: 80%
“…T and E 2 implants were used because past studies in our lab indicate that in captivity, un-implanted birds are slow to exhibit the full suite of behaviors typical of the breeding season. Past data using this treatment in a separate group of males resulted in T concentrations of 1539.96 pg/ml, sd = 711.68, n = 17 (Heimovics et al, 2011), which is within the physiological range observed in studies of wild caught starlings during the breeding season (Dawson, 1983; Riters et al, 2002). For implant surgery, we lightly anesthetized each bird using isoflurane gas anesthesia, and made a small incision in the skin just posterior to the last rib on the left side.…”
Section: Methodssupporting
confidence: 67%
“…1), both of these regions are also rich in noradrenergic alpha-2 receptors and the norepinephrine synthesizing enzyme dopamine beta hydroxylase (DBH; (Heimovics et al, 2011; Heimovics and Riters, 2008; Mello et al, 1998; Waterman and Harding, 2008)). DBH immunolabeled fibers in both GCt and VTA are found in close apposition to area X projecting neurons (Castelino et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in this species, a sizeable amount of studies have provided import insights into the physiological and neural basis underlying variation in song rate, both inside and outside the breeding season [8], [10], [11], [12]. The function and information content of song rate outside the breeding season is, however, not well understood.…”
Section: Discussionmentioning
confidence: 99%